Effects of captopril (SQ 14, 225) in a patient with primary pulmonary hypertension. Issue 664 (February 1981) - Horowitz, J. D.; Brennan, J. B.; Oliver, L. E.; Harding, D.; Goble, A. J.; Louis, W. J.
Abstract : In a 33-year-old patient with severe primary pulmonary hypertension, the acute administration of the angiotensin-converting-enzyme inhibitor captopril (SQ 14, 225) induced a rise in cardiac output, and a fall in both pulmonary and systemic vascular resistance. Subsequent chronic oral administration of captopril induced only transient clinical improvement, and the patient died. Captopril may nevertheless be useful in the treatment of less advanced cases of this disease.